Ultrasonic Automatic Tracking System - Dai Juan; Zhao Zhihong; Yan Minglian (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Ultrasonic ranging system has many characteristics, such as well-directionality, small volume, and low price, but fails to realize a long distance measured. In order to realize exactly locating motion objects, multiple ultrasonic sensors are adopted to measure their motion orientation so that their 2D coordinates should be located and positioned, which results in calculations complicated and meanwhile measurement subject to errors. This study addresses a measurement method to realize automatically tracking motion objects. It has a reasonable distribution structure of the ultrasonic sensors adopted, critical tracking calculation method, which makes it possible to solve complex problems of equations. As it has simple control instruction sequence, it is able to precisely control timing period and effectively solve measure error caused by irregular delay from commands. These programs and methods are well deployed in the parameters collection and status control system for a moving object. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5449